(untitled) (Jurnal Keamanan Nasional, 2024)
Separatist groups in the Papua and West Papua Provinces are still carrying out their actions, ranging from gunfights with security forces to attacks on civilians. The security forces find it difficult to deal with the separatist group’s actions because of differences in their ability to control the terrain or territory, in this case the separatist group has more control over the field than the security forces. This study will answer these problems by providing alternative solutions in the form of using remote sensing from an intelligence perspective. This study uses a qualitative descriptive approach using data in the form of aerial photos and the results of processing the Google Earth application. The results of intelligence analysis on the benefits of remote sensing to understand the actions of separatist groups in the Papua and West Papua regions show that it is important to use remote sensing to understand phenomena or events that occur in Papua and West Papua, especially in mountainous areas. The use of remote sensing is part of early efforts to support the national defense system.